Sentinel monitoring of activity of out-of-hours services in Norway in 2007: an observational study - Zakariassen Erik; Hansen Elisabeth; Hunskaar Steinar (BMC, 2009)
Abstract Background In Norway, no valid activity statistics from the primary health care out-of-hours services or the pre-hospital emergency health care system have previously been available. Methods The National Centre for Emergency Primary Health Care has initiated an enterprise called "The Watchtowers" which consists of a representative sample of seven casualty clinics covering 18 Norwegian municipalities. The purpose of the project is to provide routine information over several years, which will enable monitoring, evaluation and comparison of the activities in the out-of-hours services. This paper presents data from 2007, the first full calendar year for the Watchtowers, analyzes some differences in user patterns for the seven casualty clinics involved, and estimates national figures for the use of casualty clinics and out-of-hours services in Norway. Results A total of 85 288 contacts were recorded during 2007 [399 per 1 000 inhabitants] of which 64 846 contacts were considered non-urgent [76.6%]. There were 53 467 consultations by a doctor [250 per 1 000], 8 073 telephone consultations by doctor [38 per 1 000], 2 783 home visits and call-outs by doctor [13 per 1000] and 20 502 contacts managed by nurses on their own [96 per 1000]. The most common mode of contact was by telephone. Women, young children and elderly had the highest rates of contact. Conclusion Norway has a high rate of contacts to the out-of-hours services compared with some other countries with available data. Valid national figures and future research of these services are important both for local services and policy makers.